2019
DOI: 10.1108/ilt-05-2018-0211
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamic study on the tribological performance of dimple-textured surface fabricated using the turning process

Abstract: Purpose This study aims to simulate the influence of surface texturing produced via turning process toward pressure distribution and load capacity generation using computational fluid dynamics (CFD). Design/methodology/approach The dimple geometry was obtained via turning process, to be used for future application on piston skirt surfaces. Two cases were studied: a preliminary study using single periodic dimple assuming linear dimple distribution and an application study using multiple periodic dimples to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…Although rather large, the dimple geometry from Figure 1 with an area ratio of 9.9% and aspect ratio (dimple depth over width) of 0.16 is still approaching the range which can produce a positive effect under hydrodynamic lubrication. 8,38 Moreover, the dimple size was also within those derived by earlier researchers to significantly affect the tribological performance. 28,29,36…”
Section: Methodssupporting
confidence: 75%
See 2 more Smart Citations
“…Although rather large, the dimple geometry from Figure 1 with an area ratio of 9.9% and aspect ratio (dimple depth over width) of 0.16 is still approaching the range which can produce a positive effect under hydrodynamic lubrication. 8,38 Moreover, the dimple size was also within those derived by earlier researchers to significantly affect the tribological performance. 28,29,36…”
Section: Methodssupporting
confidence: 75%
“…CFD simulation on the dimple textured surface found that the dimple was able to generate the much-needed positive hydrodynamic pressure and load-carrying capacity, with the potential of separating the sliding surfaces compared to the smooth untextured surface. 38 This is supported by experimental results, in which the dimple textured surface produced by DAT generates up to 56% lower friction compared to the smooth surface when sliding on a reciprocating tribometer. 39 However, multiple dimple models should be used in the simulation instead of a single dimple model, due to more accurate representation of hydrodynamic performance considering the arrays of dimple itself.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The area ratio is used to control the pit radius. Referring to previous research (Abdul Rahman et al , 2019; Sadeghi et al , 2019), the pit radius is most appropriate to be controlled within 0.2–0.5 mm. The depth of the pit is controlled by the ratio of depth to diameter.…”
Section: Energy Consumption Calculation Model Of Textured Piston Pairmentioning
confidence: 95%
“…The measurements for dimple structure geometry in this research were length, width, depth, area ratio and aspect ratio. Calculation for area ratio ( a r ) was based on equation (1) (Abdul Rahman et al , 2019): …”
Section: Methodsmentioning
confidence: 99%